Pengaruh Penjualan Dan Biaya Produksi Terhadap Laba Bersih Pada Perusahaan Sektor Pertanian Yang Terdaftar Pada Di Bursa Efek Tahun 2019-2022 - Rahmat Syahrul; Renil Septiano (Jurnal Mutiara Ilmu Akuntansi, 2024)
Net Profit is the profit obtained after deducting tax. In more detail, this profit is the profit obtained from the difference in income and costs that have been deducted by tax. This research aims to determine the effect of Sales (X1) and Operational Costs (X2) on Net Profit in agricultural sector companies on the Indonesian Stock Exchange. The method used in this research is quantitative using secondary data in the form of annual financial reports of agricultural sector companies for the period 2019 - 2022. The analysis technique used is Panel Data Regression. Based on the research results, it shows that Sales (X1) has a positive influence on Net Profit. Sales are a company that determines the level of net profit of a company and Operational Costs (X2) Operational Costs have a negative effect on Net Profit. Operational costs are the company's ability to increase long-term costs. The level of operational costs can be a factor that has a real influence on the level of net profit that will be obtained.